Determination of zinc and manganese in local rice and evaluation of their dietary intake - Kong, Soon Hong. (Universiti Malaysia Sarawak, (UNIMAS), 2015)
A total of 28 types of rice samples that consisting of different brown rice and white rice samples were purchased from Kuching local market and collected from Nuclear Agency Malaysia, Selangor in order to analyze for manganese and zinc. Analysis and determination of zinc and manganese as focused were performed by using Atomic Absorption Spectrometry (AAS). Throughout the process, different concentration of manganese from different rice samples was ranged from 0.52 mg/kg to 1.52 mg/kg while the concentration of zinc was recorded at 0.58 mg/kg to 2.16 mg/kg. The results depicted Sarawak rice contained substantially higher manganese concentration than Selangor rice while have lower content of zinc when compare with Selangor rice. The dietary intake of manganese and zinc among Malaysian were estimated at 0.86 mg/day and 1.38 mg/day, respectively. It was concluded that, for both dietary intake of manganese and zinc among Malaysian were fall within the range of acceptable value of consumption for many countries and the Recommended Nutritional Intake (RNI) suggested by Ministry of Health, Malaysia as well as Dietary Reference Intake (DRIs) proposed by Institute of Medicine National Academics of Sciences.